2020
DOI: 10.3390/children7060052
|View full text |Cite
|
Sign up to set email alerts
|

Transient Abnormal Myelopoeisis and Mosaic down Syndrome in a Phenotypically Normal Newborn

Abstract: Transient abnormal myelopoiesis (TAM) is a common and potentially fatal neonatal complication of newborn babies with Down syndrome (DS). Children born with mosaic DS are also at risk of developing TAM. However, due to their variable phenotypes, early identification of patients with mosaic DS may be difficult; thus, early diagnosis of TAM is just as challenging. In this report, we describe a case of a phenotypically normal newborn who presented with concerns for neonatal leukemia. The diagnosis of mosaic DS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Finally, GATA1 mutations, which are characteristic of DS-AMKL, can also be found in 9% of non DS-AMKL; trisomy 21 is a constant feature in these cases, raising the possibility of constitutional mosaicism for trisomy 21, as demonstrated in 1/10 of these cases with available non-hematopoietic tissue [ 63 ]. Of note, similar findings have been reported in TAM occurring in phenotypically normal newborns, and thus suggests a search for constitutional trisomy 21 mosaicism in these cases [ 147 ].…”
Section: Special Considerations: Fab Subtype (M7) Age Predispositionsupporting
confidence: 81%
“…Finally, GATA1 mutations, which are characteristic of DS-AMKL, can also be found in 9% of non DS-AMKL; trisomy 21 is a constant feature in these cases, raising the possibility of constitutional mosaicism for trisomy 21, as demonstrated in 1/10 of these cases with available non-hematopoietic tissue [ 63 ]. Of note, similar findings have been reported in TAM occurring in phenotypically normal newborns, and thus suggests a search for constitutional trisomy 21 mosaicism in these cases [ 147 ].…”
Section: Special Considerations: Fab Subtype (M7) Age Predispositionsupporting
confidence: 81%
“…There are other reports of newborns with TMD without other clinical features of Down syndrome who had mosaic trisomy 21 in blood and bone marrow at diagnosis ( Bhatt et al 1995 ; Rozen et al 2014 ; Prudowsky et al 2020 ). In some of these reports, the mosaicism persisted after the TMD had resolved ( Bhatt et al 1995 ), but in others, once the TMD has resolved, trisomy 21 could not be identified in the blood ( Rozen et al 2014 ; Prudowsky et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…9 Neonates with T21 mosaicism are at risk for T21associated complications, such as TAM, in affected tissues, though recognition of this entity can be challenging in the absence of phenotypic features of DS. 7,8 In most cases, there is extinction of the abnormal myeloid clone early in infancy, and TAM selfresolves within months. 10 Cytoreductive treatment with leukapheresis or chemotherapy may be necessary in cases of life-threatening complications such as cardiorespiratory compromise, hyperleukocytosis, renal or liver dysfunction, disseminated intravascular coagulopathy, hydrops fetalis, or hyperviscosity.…”
Section: Figure and Table Count: 1 Figure 1 Table Reference Count: 22mentioning
confidence: 99%